Oral Findings and Salivary Alpha-Amylase in Major Depressive Disorder Patients - Al-Thabhawee, Ameer; Zaidan, Taghreed F.; Ali, Mohammed (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The increasing global prevalence of major depressive disorder (MDD) has become an important challenge, leading to a heightened demand for oral medicine in developed nations. This demand arises from the recognition of the association between psychiatric disorders and other conditions, including various orofacial pain disorders. Objective: This study are to evaluate oral conditions such as recurrent aphthous ulcers, burning mouth syndrome, and altered taste and to assess salivary alpha-amylase in individuals diagnosed with major depressive disorder. Methods: This research uses a cross-sectional study design that includes a sample of 49 patients who have been diagnosed with major depressive disorder and who have undergone treatment for at least two weeks. The control group consists of 34 healthy subjects with no signs or symptoms of systemic disease. The study group received the diagnosis in Najaf City according to the criteria in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). With respect to recurrent aphthous ulcers, the results of this study show the percentage of patients with oral ulcers is significantly higher than in the control group. Results: The results also show that the prevalence of burning mouth syndrome is significantly higher in patients with major depressive disorder than in healthy controls. A highly statistically significant difference was found between the study group and the control group regarding altered taste. There is also a significant difference in salivary alpha-amylase levels between the study and control groups (p = 0.009). Conclusion: Major depressive disorder patients have much higher incidences of reported recurrent aphthous ulcers, burning mouth syndrome, and altered taste than healthy subjects, indicating the importance of psychological factors in these conditions. Additionally, salivary alpha-amylase levels were higher in patients with major depressive disorder than in the control group.